Immunization with PfGBP130 generates antibodies that inhibit RBC invasion by P. falciparum parasites - Johnson, Yannick; Shakri, Ahmad Rushdi; Pond-Tor, Sunthorn; Jnawali, Anup; Najrana, Tanbir; Wu, Haiwei; Badhai, Jhasketan; Alameh, Mohamad-Gabriel; Weissman, Drew; Kabyemela, Edward; Duffy, Patrick; Fried, Michal; et al. (Frontiers in Immunology, 2024)
Background Despite decades of effort, Plasmodium falciparum malaria remains a leading killer of children. The absence of a highly effective vaccine and the emergence of parasites resistant to both diagnosis as well as treatment hamper effective public health interventions. Methods and results To discover new vaccine candidates, we used our whole proteome differential screening method and identified PfGBP130 as a parasite protein uniquely recognized by antibodies from children who had developed resistance to P. falciparum infection but not from those who remained susceptible. We formulated PfGBP130 as lipid encapsulated mRNA, DNA plasmid, and recombinant protein-based immunogens and evaluated the efficacy of murine polyclonal anti-PfGBP130 antisera to inhibit parasite growth in vitro. Immunization of mice with PfGBP130-A (aa 111–374), the region identified in our differential screen, formulated as a DNA plasmid or lipid encapsulated mRNA, but not as a recombinant protein, induced antibodies that inhibited RBC invasion in vitro. mRNA encoding the full ectodomain of PfGBP130 (aa 89–824) also generated parasite growth-inhibitory antibodies. Conclusion We are currently advancing PfGBP130-A formulated as a lipid-encapsulated mRNA for efficacy evaluation in non-human primates.